Online Loan Application against Islamic Sharia from the Informatics Aspect - Aulia Faqih Rifai; Agung Fatwanto (Global Review of Islamic Economics and Business, 2022)
In discussing social and organizational change, religion is one important aspect that is often overlooked despite its significant role in social life and society. Religion influences culture, customs, behavior, and communication. Several studies on the use of information technology based on religion have been carried out with a case study approach in areas such as education, economics, and health. However, none of them have incorporated the religious aspect in the application design. One of the information technology and economic products that is closely related to everyday life is online loan applications. Many studies have been conducted on online loan applications in terms of law, economics, and psychology, but they have not explored Islamic Sharia-based on informatics aspects. As the main foundation for online loan applications, informatics should be the basis of studies used to consider making regulations for both general and Islamic Sharia. This study aims to conduct an in-depth analysis of Islamic Sharia values in online loan applications related to the informatics aspect. Based on the laws of OJK (Financial Services Authority) and the fatwas of MUI (Majelis Ulema Council) regarding online loan applications, it has been found that applications legally registered with the OJK have complied with Islamic Sharia as stipulated by the MUI. However, in illegal online loan applications, many detrimental problems are found that do not comply with Islamic Sharia. Therefore, it is deemed necessary to take action in the form of regulations, social education, and support for religious knowledge to address these online loan issues.